Rough justice the DC comics sketches of Alex Ross - Ross, Alex (Pantheon Books, 2010)
Private sketchbooks of the author reveal his pencil and ink drawings of DC Comics characters, nearly all of them appearing in print here for the first time. Includes deleted scenes and altered panels for the epic Kingdom Come saga, proposals for revamping classic properties as Batgirl, Captain Marvel, and an imagined son of Batman named Batboy, and unused alternate comic book cover ideas for the monthly Superman and Batman comics of 2008-2009.